Application of 10% Ascorbic Acid Improves Resin Shear Bond Stregth in Bleached Dentin - Kamizar, Kamizar; Suprastiwi, Endang; Heptorina, Yusi (UI Scholars Hub, 2014)
Restoration of the teeth immediately after bleaching with H2 O2 35% is contraindicated due to the remnants of free radical that will stay inside dentin for 2-3 weeks which will compromise the adhesiveness of composite resin. Objective: The aim of this study was to evaluate the influence of 10% ascorbic acid on shear bond strength of composite placed on bleached dentin. Methods: Twenty seven samples were divided equally into three groups. Group 1: dentin was etched with 35% phosphoric acid; Group 2: dentin was bleached with 35% H2 O2 followed by etching with 35% phosphoric acid; Group 3: dentin was bleached with 35% H2 O2 , followed by application of 10% ascorbic acid and etched with 35% phosphoric acid. All samples were then stored at 370 C for 24 hours. The Universal Testing Machine was used to measure shear bond strength and the results were analyzed with Kruskal Wallis and Mann Whitney test. Results: After nine independent experiments, 10% ascorbic acid application on bleached dentin resulted in highest increased in bond stregth (56.04±11.06MPa) compared to Group 2 (29.09±7.63MPa) and Group 1 (25.55±2.22MPa) and the difference was statistically significant (p